American patriotism in poems and prose - Begley, Ed 1901-1970; Harris, Julie 1925-2013; O'Neal, Frederick 1905-1992; Sackler, Howard (Caedmon Records, 1966)
Includes readings of famous song and speeches as well as well-known American patriotic poems
Keywords: American poetry; Patriotic poetry, American